ANALISIS EKONOMI TERHADAP PENYELESAIAN PELANGGARAN HAK CIPTA INDONESIA - Budi Agus Riswandi (Journal of Management and Business, 2005)
Indonesian law for intellectual property right is establish in UU No. 19 Tahun 2002. This law is one of the law that categorized in economic scope. According to the scope this law should be able to stimulate and develop Indonesian economy. One of the measurement of the objective achievement of this law is by doing economy analysis for this law. This paper will discuss economy analysis for this law regarding to the benefit aspect, especially in law enforcement.